200k views
3 votes
(x – 3)³
Given: (x – y)³ = x³ – 3x²y + 3xy² – y³

1 Answer

1 vote

ANSWER


{(x - 3)}^(3) = {x}^(3) - 9 {x}^(2) + 27x - 27

Step-by-step explanation

We want to expand:


{(x - 3)}^3

Using the identity;


{(x - y)}^(3) = {x}^(3) - 3 {x}^(2)y + 3x {y}^(2) - {y}^(3)

We substitute y=3 into the above identity to obtain:


{(x - 3)}^(3) = {x}^(3) - 3 {x}^(2)(3) + 3x( {3}^(2) ) - {(3)}^(3)

Let us simplify to get:


{(x - 3)}^(3) = {x}^(3) - 9 {x}^(2) + 27x - 27

User IkePr
by
5.7k points